ANALISIS PENERAPAN GREEN ACCOUNTING PADA KINERJA KEUANGAN PT UNILEVER INDONESIA TBK - Sukmono, Sigit; Kuncara, Tommy; Immi Fiska Tarigan; Ayanto, Hana Kamilia (Asosiasi Dosen Muda Indonesia, 2023)
This research was written with the aim of analyzing the application of Green Accounting at PT Unilever Indonesia Tbk. The background of this writing is because the author wants to analyze green accounting or Green Accounting at the company PT Unilever Indonesia Tbk, whether the implementation is good or not. The method used in this study is the Document Study method. The results of this study indicate that PT Unilever Indonesia Tbk has implemented Green Accounting very well and is also committed to implementing Green Accounting every year. The costs incurred by PT Unilever Indonesia Tbk in implementing Green Accounting in 2019 – 2021 amount to IDR 284,842,399,000. In implementing Green Accounting, PT Unilever Indonesia Tbk only focuses on 4 aspects namely; Economic Aspect, Environmental Aspect, Social Aspect, Health Aspect. On the economic aspect, PT Unilever Indonesia Tbk one of which is training and development for its employees. On the environmental aspect, PT Unilever Indonesia Tbk's sustainable activities that are always carried out annually are waste banks. On the social aspect, PT Unilever Tbk carries out cleaning activities and other social activities. In the health aspect, PT Unilever Indonesia provides health education services to the community.